2006
DOI: 10.1002/jobm.200510513
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nif genes in N2‐fixing bacterial strains isolated from rice fields along the Yangtze River Plain

Abstract: The aim of this research was to identify nifH and nifHDKYE ' genes in twenty strains of N2-fixing heterotrophic bacteria isolated from rice fields in the Yangtze River Plain. Southern hybridization of the total DNA from each strain was performed with the Klebsiella pneumoniae nifHDKYE ' gene probe (6.2 kb Eco RI fragment from pSA30) and the Azospirillum brasilense nifH gene probe (0.6 kb Eco RI-Hin dIII fragment from pHU8). We found that Eco RI fragments of total DNA from Aeromonas hydrophila HY2, Bacillus azo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 24 publications
2
16
0
1
Order By: Relevance
“…In the phylum Firmicutes, isolates UFLA85 and UFLA94 were more similar to Bacillus subtilis, with 99 % and 97 % 16S rDNA sequence similarity, respectively; additionally, UFLA75 was more similar to B. cereus and B. thuringiensis, with 94 % sequence similarity. The genus Bacillus is also known to have nitrogen-fixing species, including B. cereus and B. subtilis (Xie et al, 1998;Ding et al, 2005;Xie et al, 2006). In our study, all Bacillus isolates exhibited acetylene reduction indicating the presence of nitrogenase.…”
Section: Resultssupporting
confidence: 57%
“…In the phylum Firmicutes, isolates UFLA85 and UFLA94 were more similar to Bacillus subtilis, with 99 % and 97 % 16S rDNA sequence similarity, respectively; additionally, UFLA75 was more similar to B. cereus and B. thuringiensis, with 94 % sequence similarity. The genus Bacillus is also known to have nitrogen-fixing species, including B. cereus and B. subtilis (Xie et al, 1998;Ding et al, 2005;Xie et al, 2006). In our study, all Bacillus isolates exhibited acetylene reduction indicating the presence of nitrogenase.…”
Section: Resultssupporting
confidence: 57%
“…We did not find any evidence for nifH in B. simplex 30N-5 despite the fact that we based our primer set on data from [41] and that several reports were published earlier regarding nifH presence in various Bacillus genomes [41][42][43]. We also found no evidence for nif genes in an analysis of a draft sequence of the B. simplex genome.…”
Section: Nitrogen Fixation Testsmentioning
confidence: 42%
“…Thus, the discovery of Bacillus hosted in the shoot of sugarcane open several possibilities to promote plant growth with this genus. These bacteria present high genetic diversity and agricultural relevance (McSpadden Gardener, 2004), mainly for presenting nitrogenase activity in some species, such as B. subtilis, B. pumilus, and B. megaterium (Xie et al, 1998). A previous study has reported that many species of Bacillus can contribute significantly to the plant growth (Davolos et al, 2015).…”
Section: Resultsmentioning
confidence: 99%